KELAYAKAN PENGEMBANGAN JARINGAN JALAN UNTUK MENDUKUNG INDUSTRI PERTANIAN DI KABUPATEN SUMBAWA BARAT - Serena, Agita Risty; Santosa, Wimpy (FSTPT Indonesia, 2015)
Transportation is one of the main points in fulfilling daily necessities of goods and services by using existing infrastructures for a particular purpose. Regency road is road that connected regencies or cities with the center of activities in an area. Development of regency road expected to gives contribution for development and equity of construction in that area. This study aims to analyze the feasibility of regency road network to support agricultural sector and to determine NPV value and BCR value of the eastern and southern ring roads of West Sumbawa Regency. Data used in this study is road length, population, and Gross Domestic Product of each production sector from 2008 until 2011. Methods used in this study are the Producer Surplus Method, NPV, and BCR. The analysis shows that eastern and southern ring roads that support agricultural sector in West Sumbawa Regency have a positive NPV value and BCR value is greater than 1, meaning that the road development is feasible.